A "Folk Biology" of racial theory? Psychology and the historiography of 18th-century race thought - Newberry, George T. (History compass, 2018)
Human racial kinds have been disproven by genetic and anthropological analysis. A historiographical consensus has accordingly arisen over the last few decades which sees race thought and racism as historically specific inventions, the genesis of which occurred during or after the Enlightenment. At the same time, this historical narrative has achieved dominance, work in the field of psychology has argued essentialist, categorical thinking about human kinds to be an innate component of human psychology—perhaps with a root in an evolutionary "folk biology." These two disciplines thus appear fundamentally at odds over the origins of racial thought. This article outlines the arguments for both models and offers some commentary on how future historical work might be interact with the psychological model as it looks back into the early modern period.